KOMIK DIGITAL BERBASIS KEARIFAN LOKAL BALI “SUBAK” PADA MATERI EKOSISTEM UNTUK MENINGKATKAN LITERASI SAINS KELAS V SD - Utari Mega Pratiwi, Made; I Gede Margunayasa; Dewi Arum Widhiyanti Metra Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of scientific literacy among elementary school students indicates that science and social learning has not optimally connected ecosystem concepts with real-life contexts. The limited use of interactive learning media integrating technology and local culture results in low student engagement and difficulties in understanding scientific phenomena contextually. This study aims to develop, validate, analyze practicality, and evaluate the effectiveness of a digital comic based on Balinese local wisdom Subak on ecosystem material to improve fifth-grade students’ scientific literacy. This research employed a Research and Development approach using the ADDIE model with a one group pretest–posttest design. The subjects consisted of 2 material experts, 2 media experts, 2 teachers, 6 students in practicality testing, and 22 students in effectiveness testing. Data were collected using validity and practicality questionnaires and a 20-item multiple-choice scientific literacy test. Data analysis applied descriptive quantitative techniques and paired samples t-test after normality and homogeneity assumptions were met. The results showed validity scores of 4.8 from material experts and 4.9 from media experts categorized as highly valid, while practicality reached 99% from teachers and 96% from students. Effectiveness testing obtained a significance value of 0.000 (<0.05), indicating a significant increase in students’ scientific literacy. Therefore, the developed digital comic is valid, practical, and effective for supporting meaningful science learning through technology and local culture integration.